2020
DOI: 10.1186/s12913-020-05821-2
|View full text |Cite
|
Sign up to set email alerts
|

Parent’s perspectives of the pathway to diagnosis of childhood cancer: a matter of diagnostic triage

Abstract: Background Early diagnosis is crucial for the treatment of childhood cancer as it in some cases can prevent progression of disease and improve prognoses. However, childhood cancer can be difficult to diagnose and barriers to early diagnosis are multifactorial. New knowledge about factors influencing the pathway to diagnosis contribute to a deeper understanding of the mechanisms that influence this time span. Qualitative research in the field is sparse but can be expected to lead to additional u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 52 publications
3
19
0
Order By: Relevance
“…Parental delays in childhood cancer are closely related to parental health‐seeking behavior. Parents are the individuals who first notice a physical or behavioral change in their children and initiate the diagnostic childhood pathway, so their perspective and behavior, especially in health‐seeking behavior, will affect the interval of diagnostic triage 58 . Our findings from the theoretical framework described the concept of the determinant of parental use of CAM, which includes vague initial childhood cancer symptoms, parental seeking behavior, CAM availability/accessibility, and barrier of healthcare facilities, could be classified as internal and external factors 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Parental delays in childhood cancer are closely related to parental health‐seeking behavior. Parents are the individuals who first notice a physical or behavioral change in their children and initiate the diagnostic childhood pathway, so their perspective and behavior, especially in health‐seeking behavior, will affect the interval of diagnostic triage 58 . Our findings from the theoretical framework described the concept of the determinant of parental use of CAM, which includes vague initial childhood cancer symptoms, parental seeking behavior, CAM availability/accessibility, and barrier of healthcare facilities, could be classified as internal and external factors 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed research has shown that SEP of the parents may influence the clinicians’ approach; how they involve the parents in the clinical setting [ 16 ], and which themes are addressed in the consultation [ 45 ]. The doctor-patient/parent relationship in the prediagnostic period of childhood cancer has been explored in qualitative studies [ 13 , 16 , 45 47 ] including parents with different level of SEP describing differences in proactive and strategic roles in the process of obtaining a diagnosis [ 13 , 46 , 47 ]. A recent Danish interview study ( N = 46) described this as a mechanism where some parents take advantage of their health-relevant cultural capital [ 48 ] in the process of obtaining a diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The strategic approach enabled them to negotiate with their GP, e.g. about further diagnostic tests and thereby speeding up the process of obtaining a diagnosis [ 47 ]. As health-relevant cultural capital is related to the SEP [ 48 ] of individuals, this mechanism may contribute to explaining our findings that children with parents of short education, looser affiliation to the work market and with depression have a higher risk of frequent contacts prior to diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there was strong consensus regarding the best practice of conducting the consultation, taking into account parental concern or instinct which has been shown to be an important factor in diagnosis of childhood cancer 19 20. Referral pathways for childhood cancers include an urgent referral process for suspected cancer but has been subject to criticism.…”
Section: Discussionmentioning
confidence: 99%